Active social policies in the EU : inclusion through participation? - Berkel, Rik van; Møller, Iver Hornemann (Policy Press, 2002)
This book challenges the underlying presupposition that regular employment is the royal road to inclusion. Drawing on original empirical research, it investigates the inclusionary and exclusionary potentials of different types of work, including activation programmes.